Direct valorization of cellulose to glycolic acid through green heteropoly acid catalyst supported on tin (iv) oxide - Chan, Jun Jie (2025)
This study focuses on the catalytic conversion of cellulose, a renewable and abundant component of lignocellulosic biomass, into glycolic acid, a valuable compound with wide industrial applications. Using phosphomolybdic acid (PMA) supported on tin (IV) oxide (SnO₂) as a heterogeneous catalyst, the research investigates the optimization of glycolic acid synthesis under mild reaction conditions. The study explores the influence of PMA loading on the physicochemical properties of the catalyst and evaluates its catalytic performance in the presence of hydrogen peroxide (H₂O₂) as an oxidant. Characterization techniques such as FTIR, XRD, FESEM-EDS, N₂-physisorption and pyridine adsorption reveal the role of PMA in enhancing surface area, acidity, catalytic efficiency and active sites. The optimized process achieves a high glycolic acid yield of approximately 60% with minimized by-products, demonstrating the bifunctional catalytic behavior of PMA for acid hydrolysis and oxidative cleavage. Systematic parameter studies highlight the importance of reaction time, pH, and oxidant concentration in maximizing yield and selectivity. Additionally, the study confirms the reusability and stability of the PMA/SnO₂ catalyst, showcasing its potential for scalable and sustainable industrial applications. Recommendations for future work include exploring alternative cellulose sources, employing advanced characterization techniques, testing other green oxidants, and conducting reproducibility experiments to validate data. This research contributes to the development of efficient and environmentally friendly processes for biomass valorization, aligning with global sustainability goals.